Relevansi Kaidah Fikih Siyasah terhadap Perdamaian Global dan Hubungan Internasional Modern - Bahrul Ulum Al Fauzi Ainul Yaqin; Rosalina Cahya Safitri; Siti Sofiatun Ningsih; Nanda Sania Al Mubarok (CV. ITTC INDONESIA, 2025)
This article examines the crucial role of treaties in fostering peace and international cooperation from the perspective of fiqh siyasah (Islamic political jurisprudence). The discussion focuses on three fundamental legal maxims in international relations according to Islam: al-aslu fi al-mu‘ahadat al-istimrār (the default ruling for treaties is continuity), al-aslu fi al-‘alāqah al-silm (the default in relationships is peace), and as-sulh ‘an al-ḥudūd bāṭil (reconciliation does not apply to hudud punishments). This study employs a normative-theological approach by examining the Qur’anic and Hadith-based foundations of these principles and their implementation in modern statecraft and international diplomacy. The findings indicate that these maxims not only have strong theological roots but also practical relevance in maintaining stability, ensuring justice, and preventing global conflict. The article recommends integrating these principles of fiqh siyasah into the foreign policies of Muslim-majority countries as a contribution to global peacebuilding.